PRESUPPOSITION IN THE JAKARTA POST’S POLITICAL ARTICLES: A PRAGMATICS APPROACH - Fahrus Zaman Fadhly; Ayu Putri Kurnia (University of Kuningan, 2015)
This study is aimed to investigate presupposition in The Jakarta Post daily newspaper’s articles in political column. It covers two problems: types of presupposition and triggers of presupposition. Those problems were identified by applying presupposition theory. The data were interpreted by using descriptive qualitative method since it intended to describe a large number of sentences, clauses and phrases rather than numbers. The result of the study showed that the most frequent was existential presupposition with 202 occurences (78.59%), followed by factive presupposition with 2 occurences (0.79%), lexical presupposition with 36 occurences (14%), structural presupposition with 11 occurences (4.28%), non-factive presupposition with 2 occurences (0.79%) and counterfactual presupposition with 4 occurrences (1.56%). Besides, the study also showed the existence of 691 presupposition triggers which consisted of 631 definite descriptions (90.92%), 2 factive items (0.28%) which was similar to the existence of change of state verbs, 6 implicative verbs (0.86%), 6 itteratives (0.86%), 21 temporal (3.02%), 13 comparisons and contrast (1.87%), 8 questions (1.15%) and 3 counterfactual conditionals (0.43%). Finally, the findings showed that both types and triggers of presuppositions were related each other.Keywords: presupposition, types of presupposition, triggers of presupposition, political column, The Jakarta Post.